Expressed Emotion Towards Individuals with Mental and Physical Health Conditions: A Structured Literature Review - Zasiekina, Larysa (East European Journal of Psycholinguistics, 2018)
Expressed Emotion (EE) is a well-validated measure of the family environment of individuals with mental and physical conditions that examines relatives’ critical, hostile and emotionally overinvolved attitudes towards a family member with a condition. This review focuses on studies of EE on containing data of the impact of Expressed Emotion on the course of chronic illnesses and clinical outcomes in mental and physical health conditions. The structural literature review is based on the search of articles in peer-reviewed journals from 1991 to November, 2018 in the databases Psyc-Info and PubMed. Taken together, these results suggest that there is an association between EE towards patients with both physical and mental conditions and  a poor clinical and personal recovery. Interestingly, the lower levels of EE towards individuals with a condition were observed  in partners comparatively with parents, adult children and relatives. However, the results have been obtained only from two populations with dementia and Type I diabetes and have been considered as important issue for future research.  ReferencesAyilara, O., Ogunwale, A., & Babalola, E. (2017). Perceived expressed emotion in relatives of patients with severe mental illness: A comparative study. Psychiatry research, 257, 137-143.Bogojevic, G., Ziravac, L., & Zigmund, D. (2015). Impact of expressed emotion on the course of schizophrenia. European Psychiatry, 30, 390.Brown, G. W., Birley, J. L. T., & Wing, J. K. (1972). Inﬂuence of family life on the course of schizophrenic disorders: A replication. British Journal of Psychiatry, 121, 241–258.Chan, K. K., & Mak, W. W. (2017). The content and process of self-stigma in people with mental illness. American Journal of Orthopsychiatry, 87(1), 34-43.Cherry, M. G., Taylor, P. J., Brown, S. L., & Sellwood, W. (2018). Attachment, mentalisation and expressed emotion in carers of people with long-term mental health difficulties. BMC Psychiatry, 18(1), 257.Coomber, K., & King, R. M. (2013). Perceptions of carer burden: differences between individuals with an eating disorder and their carer. Eating Disorders, 21(1), 26-36Engel, G. L. (1977). The need for a new medical model: a challenge for biomedicine. Science, 196(4286), 129-136.Flanagan, D. A., & Wagner, H. L. (1991). Expressed emotion and panic fear in the prediction of diet treatment compliance. British Journal of Clinical Psychology, 30, 231–240.Hooley, J. M., & Parker, H. A. (2006). Measuring expressed emotion: An evaluation of the shortcuts. Journal of Family Psychology, 20(3), 386.Rienecke, R. D., Lebow, J., Lock, J., & Le Grange, D. (2015). Family profiles of expressed emotion in adolescent patients with anorexia nervosa and their parents. Journal of Clinical Child & Adolescent Psychology, 46(3), 428-436.Safavi, R., Berry, K., & Wearden, A. (2018). Expressed emotion, burden, and distress in significant others of people with dementia. Journal of Family Psychology, 32(6), 835.Romero-Gonzalez, M., Chandler, S., & Simonoff, E. (2018). The relationship of parental expressed emotion to co-occurring psychopathology in individuals with autism spectrum disorder: A systematic review. Research in developmental disabilities, 72, 152-165.Wearden, A. J., Tarrier, N., Barrowclough, C., Zastowny, T. R., & Rahill, A. A. (2000). A review of expressed emotion research in health care. Clinical Psychology Review, 20(5), 633-666.Wearden, A. J., Tarrier, N., & Davies, R. (2000). Partners' expressed emotion and the control and management of Type 1 diabetes in adults. Journal of Psychosomatic Research, 49(2), 125-130.